Studi Literatur Gambaran Hasil Pemeriksaan Ureum Pada Penderita Tuberculosis (Tb) Paru yang Mengonsumsi Obat Anti Tuberculosis (OAT) - Tuty Widyanti; Effendy Rasiyanto; Anita Anita; Vindrawati Mooduto (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Muhammadiyah Makassar, 2021)
Pulmonary Tuberculosis (TB) is an infectious disease of the respiratory tract of the lungs caused by the bacterium Mycobacterium tuberculosis. To treat the disease by using Anti Tuberculosis Drugs (ATD) which is used for 4-6 months. Treatment time that is long enough can affect the kidneys which have an effect until the occurrence of impaired kidney function. One of the important prognostic factors to evaluate the effect of ATD is by observing kidney function using laboratory indicators such as urea examination. This study aims to determine the description of the results of urea levels in pulmonary TB patients who take ATD with the type of literature study research and data collection with library techniques. The samples in this study were journals and scientific papers related to pulmonary TB patients who took ATD with a total of 6. The method used in this study was a literature study. The results of the study were obtained based on the results of a review of 5 literatures, obtained from 167 samples, obtained normal urea levels as many as 112 (67.1%) samples and urea levels which increased by 55 (32.9%) samples so that it can be concluded that patients with tuberculosis (TB) In the lungs, especially those taking ATD, some have normal urea levels and some have an increase.